Enhanced aggressive phenotype of Tph2 knockout rats is associated with diminished 5-HT1A receptor sensitivity. (15th July 2019) - Peeters, Deborah G.A.; de Boer, Sietse F.; Terneusen, Anneke; Newman-Tancredi, Adrian; Varney, Mark A.; Verkes, Robbert-Jan; Homberg, Judith R.
Abstract: Brain serotonin (5-HT) plays a key role in aggressive behaviours and related psychopathologies, but its precise mechanism of action remains elusive. Genetic animal models may provide a tool to elucidate the relationship between aggression and serotonin. The present study showed that tryptophan hydroxylase 2 (Tph2) knockout (KO) rats, which exhibit profoundly diminished extracellular serotonin levels, display increased aggressiveness compared to their Tph2 wildtype (WT) counterparts. However, the level of aggression in Tph2 KO rats did not equal that of feral wild type Groningen (WTG) rats. To investigate whether enhanced 5-HT1A receptor functionality may be present in Tph2 KO rats, we tested the acute anti-aggressive potency of the highly selective 5-HT1A receptor full agonist NLX-112 (a.k.a. befiradol or F13640). Data show that compared to Tph2 WT and WTG rats, the NLX-112 dose-effect curve was shifted to the right in Tph2 KO animals. These results suggest that, unlike previous reports in Tph2 KO mice, Tph2 KO rats have a decreased 5-HT1A receptor sensitivity compared to both Tph2 WT and WTG animals. Highlights: Tph2 KO rats show increased aggressive behavior compared to their WT counterparts. The 5-HT1A receptor agonist NLX-112 shows a robust anti-aggressive effect. The dose-effect curve shifts rightward in Tph2 KO as compared to WT and WTG rats. This suggests a decreased 5-HT1A receptor sensitivity in Tph2 KO rats.